Longitudinal evaluation of serum neurofilament light levels in normal healthy volunteers: defining a threshold of concern - Lanz, Thomas; Ruprecht, Klemens; Somps, Christopher J.; Göpfert, Jens C.; Kam-Thong, Tony; Tekle, Fetene; Fader, Kelly A.; Yañez, Viviana A. Carcamo; Meyer, Volker; Friedrich, Sabine; Vlasakova, Katerina; Otto, Carolin; et al. (Journal of neurology, 2025)
Neurofilament light (NfL) is a neuron-specific protein integral to neuronal cytoskeletons. Upon damage to the central or peripheral nervous system (NS), NfL is released into cerebrospinal fluid and blood. Elevated serum or plasma NfL levels have been reported in a variety of diseases and NS injury states. However, although intraindividual longitudinal NfL changes may be more meaningful than NfL measurements at a single timepoint, data on the longitudinal variation of NfL in normal healthy volunteers (NHV) are scarce. We investigated normal variation in NHV serum NfL and estimate an upper limit of normal (ULN) of NfL variation in longitudinal samples. An initial cross-sectional screening in sera from 270 NHV using a 4-plex assay detected NfL in 99.6% and glial fibrillary acidic protein (GFAP) in 100%, while Tau (67.4%), and Ubiquitin Carboxyl-Terminal Hydrolase L1 (UCH-L1, 4.1%) were less frequently detectable. An age-dependent increase was found in NfL (2.36% per year) and GFAP (1.18% per year). Longitudinal evaluation of NfL was then conducted in a separate cohort of 80 NHV at baseline, day 14 (range 11-17), and day 28 (range 26-56). A 1.64-fold increase from baseline in serum NfL was calculated as the ULN. Putting this threshold into context with published reports on NfL across a large variety of injury and disease settings, the 1.64-fold threshold is well positioned to discriminate between healthy and NS injury. Altogether, these findings provide a framework for longitudinal monitoring of serum NfL as a biomarker for neuronal damage in multiple contexts of use, including drug-induced injury.
Online veröffentlicht: 15. Juli 2025
Gesehen am 26.11.2025